A contribution to the debate on the redefinition of the networked public sphere based on Portuguese public participation in cyberspace - Quintanilha, Tiago Lima (2018)
This article locates Portugal in the discussion on the transition from a normative public sphere (Habermas, 1968/1989, 1998) to a new networked public sphere (Benkler, 2006), powered by the internet, global networked society and participative and interactive cultures. We use data from the public participation module of the 2018 Digital news report published by the Reuters Institute for the Study of Journalism, which surveyed a representative sample of the Portuguese population. The results point to the existence and appropriation of many forms of public participation in cyberspace. Users share news, comment on news, take part in online votes, etc., on press websites and social media. Nonetheless, the collected data point to a type of online public participation that determines the slow constitution and consolidation of a new networked public sphere in Portugal.